Management of Crown Root Fracture by Interdisciplinary Approach - K. Radhakrishnan Nair; Anoop N. Das; Manoj C. Kuriakose; Nandakumar Krishnankutty (Case Reports in Dentistry)
Fracture of tooth after trauma is distressing to a person because of the discomfort and pain due to pulpal injury. Crown root fractures of anterior teeth cause concomitant periodontal injury and there will be concern about appearance, and aesthetics. Management of pulpal and periodontal tissue relieves pain and restoration of tooth form regains patients confidence. Restoration of fractured tooth will be accepted readily if it is minimally invasive, less expensive, and aesthetically acceptable. Reattachment is an option for restoration of anterior teeth compared to other artificial replacements because of its appearance as natural. This method is favourable when the fractured fragment is intact and available. Utilization of pulp space for retention of fragment is achieved by the insertion of a dentine bonding post. This case report describes a case of tooth reattachment after trauma in which the pulp space is utilized to bond a fiber-reinforced post for retention after periodontal tissue management.